Whistleblowing protection and freedom of speech: Finding respect at the workplace - Ahmad, Rusniah; Mohd Shariff, Roos Niza (UUM COLGIS Universiti Utara Malaysia, 2009)
Does the whistleblower have a place in business and organizations? Being a controversial figure the whistleblower’s journey is full of obstacles. The term is taken from the actions of the English police officers or “bobbies” out on their police beats reacting to the discovery of a commission of a crime where they would blow their whistle. This immediate reaction is to alert the public and other police officers of danger within their midst. Another analogy that could also be the origins of the term is the act of the referee or umpire of a football game who would blow the whistle upon discovery or seeing a foul committed by players in the game. Simply put whistle blowing is an act of correcting once a discovery of wrongdoing has been exercised. The act of a whistleblower is an expression of an important right that is the right to free speech. When an employee voices his concerns over certain issues internal to the organization he/she is exercising a right to freely voice matters that is important for the organization to look into. Even though organizations have the privilege to ignore but choosing such a cause may not be a wise move.